2018
DOI: 10.1007/s11999.0000000000000243
|View full text |Cite
|
Sign up to set email alerts
|

Does Denosumab Change the Giant Cell Tumor Treatment Strategy? Lessons Learned From Early Experience

Abstract: Background Although giant cell tumors (GCTs) are benign, their aggressiveness and tendency to recur locally challenge the orthopaedic surgeon's ability to perform joint-preserving intralesional surgery with an acceptably low risk of local recurrence. Denosumab has emerged as a possible medical treatment of GCT because it seems to halt the progression of GCT, alleviate pain, and increase perilesional bone formation, but its exact role has been questioned, and specifically its efficacy and associated complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 18 publications
1
77
0
3
Order By: Relevance
“…Residue tumor cells may hide within the new bone and thickened cortex and may recur once denosumab is discontinued [22,24,25].Traub et al [25] described that the tumor tissue was replaced by gritty, fibrous-like tissue new bone, they suggested intra-operative fluoroscopy to guide the extent of resection. On the other hand, it is argued that the newly formed peripheral bone rim and hardened tumor tissue reduced the risk of inadvertent contamination [19]. Although we did not acquire sufficient data to conduct pooled-analysis on the outcome of denosumab combining curettage and local adjuvant, it is strongly recommended in many studies to use local adjuvant and high speed burr [3,24,26,27].Most studies included in our analysis applied various methods of local adjuvant in most patients except for one study specified that no local adjuvant was used [20].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Residue tumor cells may hide within the new bone and thickened cortex and may recur once denosumab is discontinued [22,24,25].Traub et al [25] described that the tumor tissue was replaced by gritty, fibrous-like tissue new bone, they suggested intra-operative fluoroscopy to guide the extent of resection. On the other hand, it is argued that the newly formed peripheral bone rim and hardened tumor tissue reduced the risk of inadvertent contamination [19]. Although we did not acquire sufficient data to conduct pooled-analysis on the outcome of denosumab combining curettage and local adjuvant, it is strongly recommended in many studies to use local adjuvant and high speed burr [3,24,26,27].Most studies included in our analysis applied various methods of local adjuvant in most patients except for one study specified that no local adjuvant was used [20].…”
Section: Discussionmentioning
confidence: 99%
“…Complications and others 6 studies [9,13,15,19,21,22] reported denosumab-related complications, in the 388 cases treated with denosumab, no osteo-necrosis of jaw or hypocalcemia was observed. 1 study [13] reported a periapical abscess and a periodontal disease during the course of denosumab administration.…”
Section: Recurrence Free Survivalmentioning
confidence: 93%
See 3 more Smart Citations